Makna Tradisi Zakat Fitrah (Lawatino Pitaraa) dalam Pembentukan Karakter Kepedulian Sosial Masyarakat Etnik Muna - Wa Kuasa Baka; Usman Rianse; La Ode Topo Jers; Sitti Hermina; Samsul Samsul; La Ode Aris (Laboratory of Anthropology Department of Cultural Science Faculty of Halu Oleo University, 2023)
This research aims (1) to explain the procedure for implementing the tradition of zakat fitrah (known as